A new look at local ultraluminous infrared galaxies: the atlas and radiative transfer models of their complex physics. Issue 4 (22nd December 2021) - Efstathiou, A; Farrah, D; Afonso, J; Clements, D L; González-Alfonso, E; Lacy, M; Oliver, S; Papadopoulou Lesta, V; Pearson, C; Rigopoulou, D; Rowan-Robinson, M; Spoon, H W W; et al.
ABSTRACT: We present the ultraviolet to submillimetre spectral energy distributions (SEDs) of the HERschel Ultra Luminous Infrared Galaxy Survey (HERUS) sample of 42 local ultraluminous infrared galaxies (ULIRGs) and fit them with a Markov chain Monte Carlo code using the CYprus models for Galaxies and their NUclear Spectra (CYGNUS) radiative transfer models for starbursts, active galactic nucleus (AGN) tori, and host galaxy. The Spitzer IRS spectroscopy data are included in the fitting. Our Bayesian SED fitting method takes comparable time to popular energy balance methods but it is more physically motivated and versatile. All HERUS galaxies harbour high rates of star formation but we also find bolometrically significant AGN in all of the galaxies of the sample. We estimate the correction of the luminosities of the AGN in the ULIRGs due to the anisotropic emission of the torus and find that it could be up to a factor of ∼10 for nearly edge-on tori. We present a comparison of our results with the smooth torus model of Fritz et al. and the two-phase models of Siebenmorgen et al. and SKIRTOR. We find that the CYGNUS AGN torus models fit significantly better the SEDs of our sample compared to all other models. We find no evidence that strong AGN appear either at the beginning or end of a starburst episode or that starbursts and AGN affect each other. IRAS 01003−2238 and Mrk 1014 show evidence of dual AGNs in their SED fits, suggesting a minimum dual AGN fraction in the sample of 5 per cent.